The study of solar cells with back side contacts at low illumination - Gorban, A.P.; Kostylyov, V.P.; Litovchenko, V.G.; Sachenko, A.V.; Serba, A.A.; Sokolovskyi, I.O.; Chernenko, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Theoretical analysis and experimental research of Si solar cells (SC) with interdigitated back side contacts (BSC) photovoltaic parameters and photoconversion efficiency at low light level have been done in presence of floating p⁺-n junctions and isotype n⁺-n junctions on frontal (illuminated) surface. It has been found that in case of floating junction the magnitudes of short-circuit current, open-circuit voltage and efficiency, as well as of internal quantum efficiency of photocurrent can decrease significantly due to recombination in the space charge region (SCR) rather than to surface recombination. In case of isotype junction, this decrease is absent. These results allow to conclude that the floating p⁺-n junctions at the front surface of the silicon BSC SC would be appropriate for use only in case of an illumination intensity ≥ 1000 W/m².